In vitro characterization of DNA gyrase inhibition by microcin B17 analogs with altered bisheterocyclic sites - Zamble, Deborah B. (The National Academy of Sciences, 2001)
Microcin B17 (MccB17) is a 3.1-kDa Escherichia coli antibiotic that contains thiazole and oxazole heterocycles in a peptide backbone. MccB17 inhibits its cellular target, DNA gyrase, by trapping the enzyme in a complex that is covalently bound to double-strand cleaved DNA, in a manner similar to the well-known quinolone drugs. The identification of gyrase as the target of MccB17 provides an opportunity to analyze the relationship between the structure of this unusual antibiotic and its activity. In this report, steady-state parameters are used to describe the induction of the cleavable complex by MccB17 analogs containing modified bisheterocyclic sites. The relative potency of these analogs corresponds to the capacity of the compounds to prevent growth of sensitive cells. In contrast to previously reported experiments, inhibition of DNA gyrase supercoiling activity by wild-type MccB17 also was observed. These results suggest that DNA gyrase is the main intracellular target of MccB17. This study probes the structure-function relationship of a new class of gyrase inhibitors and demonstrates that these techniques could be used to analyze compounds in the search for clinically useful antibiotics that block DNA gyrase.